Cosa intendiamo per educazione, ed in particolare per educazione al paesaggio? - Kopreinig Guzzi, Cristina (Ri-Vista. Research for landscape architecture, 2015)
The paths of education and self-education to territory are here intended as instruments for shared citizenship that is active participation in its management, both in the professional practice and civil life. The choices will be done after having examined the possible development sceneries and after having chosen those ones more sustainable, that is those in which we can find an balance in the triad environment-territory-landscape. The project of education starts from a renewed look and develops the contributions of authors as Carta, Demetrio, Sparti, Zeldin, whom give particular attention to relations between humans, the historic memory and places. The objectives of the project foresee: to promote the knowledge of the triad, to create culture and consciousness of its values, to build an educational paths from specific territorial realities, to give flexible and didactic instruments for a smart and gradual operation.